Integrated energy efficiency evaluation of a multi-source multi-load desalination micro-energy network - Wang, Dan; Yu, Jiancheng; Liu, Bo; Long, Chao; Chen, Peiyu; Chong, Zhiqiang (Elsevier, 2020)
With increasing global shortage of fresh water resources, many countries are prioritizing desalination as a means of utilizing abundantly available seawater resources. Integrated energy efficiency evaluation is a scientific method for the quantitative analysis of energy efficiency based on multiple indicators and is very useful for investment, construction, and scientific decision-making for desalination projects. In this paper, the energy efficiency evaluation of the micro energy network (MEN) of desalination for multi-source and multi-load is studied, and the basic idea of comprehensive energy efficiency evaluation is analyzed. The process includes the use of a MEN model to establish an integrated energy efficiency evaluation index system, taking into consideration energy, equipment, economic, environmental, and social factors. A combined evaluation method considering subjective and objective comprehensive weights for multi-source multi-load desalination MENs is proposed to evaluate the energy efficiency of desalination and from multiple perspectives
Keywords: Evaluation Method; Index System; Integrated Energy Efficiency Evaluation; Micro-energy Network; Seawater Desalination